Novel p22 and p30 dual-proteins combination based indirect ELISA for detecting antibodies against African swine fever virus - Li, Jianda; Jiao, Jian; Liu, Na; Ren, Sufang; Zeng, Hao; Peng, Jun; Zhang, Yuyu; Guo, Lihui; Liu, Fei; Lv, Tingting; Chen, Zhi; Sun, Wenbo; et al. (Frontiers in Veterinary Science, 2023)
African swine fever virus (ASFV) infection is one of the most complex and fatal hemorrhagic viral diseases, causing a devastating loss to the swine industry. Since no effective vaccine is available, prevention and control of ASFV heavily depends on early diagnostic detection. In this study, a novel indirect ELISA was established for detecting antibodies against ASFV using dual-proteins, p22 and p30. Recombinants p22 and p30 were expressed and purified from E.coli vector system by recombined plasmids pET-KP177R and pET-CP204L. p22 and p30 were mixed as antigens for developing the indirect ELISA. Through optimizing coating concentrations of p30 and p22, coating ratio (p30: p22 = 1:3), and serum dilution (as 1:600), the established ELISA performed higher specificity, sensitivity, and repeatability against ASFV-positive serum. Furthermore, 184 clinical serum samples from suspected diseased pigs were verified the established ELISA in clinical diagnosis. The results showed that compared with two commercial ELISA kits, the established ELISA possessed higher sensitivity and almost uniform coincidence rate. Taken together, the novel indirect ELISA based on dual-proteins p30 and p22 performed a valuable role in diagnostic detection of ASFV, providing a broad insight into serological diagnostic methods of ASFV.